Localized network layer protocols in wireless sensor networks based on optimizing cost over progress ratio. - Stojmenovic, I. (IEEE Network : the magazine of global information exchange)
We present a simple framework for designing network layer protocols for sensor networks including localized routing, broadcasting, area coverage, and so on. The framework is general enough and is applicable to a variety of problems, network assumptions, and optimality criteria. Our simple framework is based on optimizing the ratio of the cost of making certain decisions (e.g., selecting a forwarding neighbor for routing) to the progress made in doing so (e.g., reduction in distance to destination). We show how to apply this general guideline for the design of hop count, power awareness, maximal lifetime, beaconless and physical-layer-based routing, minimal energy broadcasting, sensor area coverage, and multicasting protocols. Moreover, we show that in the case of routing, the best known strictly localized position-based techniques are, in almost all cases, special cases of the described general cost-to-progress ratio paradigm